As cidades e o crime : a violência urbana em "O cobrador" de Rubem Fonseca e O matador de Patrícia Melo - Ornellas, Carolinne Quintanilha (2014)
The social contrast is a lived reality in all cities of our country, and we can note its higher expression in large urban centers. It is noticed that the banalization of the crime and life is growing every day. Related to this, the objective of this dissertation is to analyze the trajectory of the protagonists of the works "O cobrador" by Rubem Fonseca and O matador by Patrícia Melo focusing mainly on violence in major urban centers. Focus is also given to the different ways they practice their crimes, the peculiar characteristics of each of the two killer profiles. The theoretical tools for this purpose includes conceptual notions and discussions on some types of violence, mainly urban, as pointed by Hannah Arendt and Zygmunt Bauman. Furthermore, it takes regard to the theory of flâneur profile defined by Walter Benjamin, because, historically, the growth of cities and the social marginalization were some of the factors that contributed to the realization of this profile. We also intend to analyze the importance of two minor characters - namely: Ana from "O cobrador" and Dr. Carvalho from O matador – in the constitution of plots and killer profiles of the protagonists of the above works.